KONSEP PENDIDIKAN ISLAM PEMIKIRAN J. MARK HALSTEAD - Nada Nazopah (eJurnal Al Musthafa, 2023)
This paper discusses the writings of J. Mark Halstead whose original title is An Islamic Concept of Education. This paper will first contain the problem of philosophy in Islam. The second section examines the resources available to explore systematically the principles of Islamic education. The third section discusses the three dimensions of Islamic Education, namely focusing on individual development, social and moral education, and knowledge acquisition. In each section of this paper will provide a brief overview of the differences between Islamic and Western perspectives in understanding Education in each of the components discussed. This paper is a literature study by collecting data from various literatures and information from available sources such as books, journals, reports, and other documents